(untitled) (Journal of the College of Basic Education, 2019)
Women are being presented in Kamala Markandaya’s novels as the center of concern. She is a famous Indian novelist in the postcolonial era and she is very famous internationally for her masterpiece “Nectar in a Sieve”1954 . Markandaya treats women’s issues and problems in her novels in a very deep way. A woman quest for identity and redefining herself finds reflection and constituted an important motif of the female characters. What helps Markandaya in drain a realistic portrayal of a contemporary woman is that having a deep insight into women’s issues. Markandaya explores and interprets the emotional responses of women and their problems with much understanding. In her novels, female characters are the chief protagonists searching for meaning and value of life. Also She presents an existential struggle of a woman in some of her novels who refuses to submit her individual self and emerges undergoing much pain and suffering. In her writing, Markandaya traces a woman’s journey in order to know herself. This journey is from self-denial to self-assertion, from self-negation to self-affirmation, and from self-sacrifice to self-realization.